The Effect of Self-Regulated Learning (SRL) on Career Maturity with Family Support as a Mediation - Yuli Novia Sari; Suryani Hardjo; Ummu Khuzaimah (CV. Media Digital Publikasi Indonesia, 2026)
This study aims to analyze the influence of self-regulated learning on career maturity of Royal Kisaran University students and examine the role of family support as a mediator variable in this relationship. The study used a quantitative approach with a non-experimental design. The study population was active final-semester students of Royal Kisaran University with a sample of 200 respondents selected using a purposive sampling technique. Data collection was conducted through an online questionnaire using the Self-Regulated Learning Scale, Career Adapt-Abilities Scale (CAAS), and Perceived Social Support–Family Scale (PSS-Fa) scales that have been adapted to the Indonesian context. Data analysis was performed using covariance-based SEM with the JASP 0.19.3.0 program. The results showed that self-regulated learning had a positive and significant effect on career maturity (β = 0.471; p < 0.001), while family support had a positive and significant effect on self-regulated learning (β = 0.492; p < 0.001), and career maturity (β = 0.487; p < 0.001). Furthermore, there was an indirect effect of self-regulated learning on career maturity through family support as a mediator (β = 0.239; p < 0.001). These findings indicate that self-regulation skills in learning and family support play a crucial role in enhancing students' readiness for the world of work. Therefore, strengthening learning independence and optimizing family support are strategic factors in developing students' career maturity.